DNA aptamers for selective identification and separation of flame retardant chemicals - Kim, Un-Jung; Kim, Byoung Chan (ELSEVIER SCIENCE BV, 2016)
Polybrominated diphenyl ethers (PBDEs) are group of chemicals which are representative persistent organic pollutants (POPs) and used as brominated flame retardants for many consumer products. PBDEs were phased out since 2009 but are still frequently observed in various environmental matrices and human body. Here, we report ssDNA aptamers which bind to BDE47, one of the PBDE congeners commonly found in various environmental matrices, and show affinity to other major tri-to hepta-BDE congeners. The PBDE specific aptamers were isolated from random library of ssDNA using Mag-SELEX. Two out of 15 sequences, based on their alignment and hairpin loop structures, were chosen to determine dissociation constant with BDE47 and showed from picomolar to nanomolar affinities (200 pM and 1.53 nM). The aptamers displayed high selectivity to the original target, BDE47, and implying general specificity to PBDE backbone with varying affinities to other congeners. Further, we showed that the use of two aptamers together could enhance the separation efficiency of BDE47 and other BDE congeners when dissolved in a solvent compared to use of single aptamer. These aptamers are expected to provide a tool for preliminary screening or quick separation of PBDEs in environmental samples prior to trace quantitative analysis. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: POLYBROMINATED DIPHENYL ETHERS; CHROMATOGRAPHY-MASS SPECTROMETRY; MAGNETIC PARTICLE IMMUNOASSAY; WATER SAMPLES; BIOSENSORS; PBDES; ENVIRONMENT; FOOD; DIAGNOSTICS; EXTRACTION